G247 Non-invasive haemoglobin measurements for assessing anaemia in kenyan school children as part of an integrated school health and nutrition programme. (27th April 2015) - Bogie, J; Eder, B; Magnus, D
Abstract : Background: Anaemia in school children is associated with impaired cognition and poor academic performance. In western Kenya around 20% of school-aged children are anaemic due to dietary insufficiencies, helminth infections and malaria. There is a need to find field-appropriate and cost-effective methods to assess anaemia in rural populations. Method: A comprehensive school health and nutrition programme was delivered to 3552 children in rural Western Kenya. Using a non-invasive Masimo-Pronto 7 device haemoglobin levels were measured biannually in a randomly selected sample of children. Consent was obtained from the schools and parents. Results: A total of 2538 haemoglobin measurements were made over the three-year pilot. Non-invasive haemoglobin measurements were easily performed by staff and well tolerated by children. Anaemia was defined as haemoglobin of less that 12g/dl. At baseline 26.9% of children were anaemic Preliminary analysis of the first round of data collection showed a significant reduction in anaemia (OR 0.25 95% CI 0.16–0.40 p= <0.001). Discussion: Non-invasive haemoglobin measuring is relatively unused in global health work despite evidence that it produces results comparable to serum testing. It is non-invasive, well tolerated by children, cheaper and simple to use. This project has shown the potential for using non-invasive haemoglobin measuring in complex health interventions and has been able to demonstrate an improvement in levels of anaemia over the first year of the pilot. Conclusion: Non-invasive haemoglobin measuring is feasible in the assessment of child health in low resource settings and will help in the evaluation of child health programmes.